2021
DOI: 10.24272/j.issn.2095-8137.2021.075
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin remodeler INO80 mediates trophectoderm permeability barrier to modulate morula-to-blastocyst transition

Abstract: Inositol requiring mutant 80 (INO80) is a chromatin remodeler that regulates pluripotency maintenance of embryonic stem cells and reprogramming of somatic cells into pluripotent stem cells. However, the roles and mechanisms of INO80 in porcine pre-implantation embryonic development remain largely unknown. Here, we show that INO80 modulates trophectoderm epithelium permeability to promote porcine blastocyst development. The INO80 protein is highly expressed in the nuclei during morula-to-blastocyst transition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…A total of 47 candidate regions spanning 4.77 Mb were identified as parallel selection signals between the two populations (Figure S3 and S4). Based on the annotation of functional genes within the potential regions under parallel selection, we found that INO80 and FZR1 associated with reproduction (Cao et al., 2021; Yamamuro et al., 2008), INS , PDE4B and LEPR related to adipose tissue deposition (Bou et al., 2014; Wang et al., 2022; Xu et al., 2022) and FAF1 involved in skeletal development (Rangkasenee et al., 2013) exhibited evidence of parallel selection (Table S5).…”
Section: Fields Pietrain Duroc European Wild Boar Overallmentioning
confidence: 99%
“…A total of 47 candidate regions spanning 4.77 Mb were identified as parallel selection signals between the two populations (Figure S3 and S4). Based on the annotation of functional genes within the potential regions under parallel selection, we found that INO80 and FZR1 associated with reproduction (Cao et al., 2021; Yamamuro et al., 2008), INS , PDE4B and LEPR related to adipose tissue deposition (Bou et al., 2014; Wang et al., 2022; Xu et al., 2022) and FAF1 involved in skeletal development (Rangkasenee et al., 2013) exhibited evidence of parallel selection (Table S5).…”
Section: Fields Pietrain Duroc European Wild Boar Overallmentioning
confidence: 99%
“…A study showed that knockdown of AP-2γ (Tcfap2c), a novel upstream regulator of Cdx2 expression, causes downregulation of Pard6b, Tjp2, Cldn4, Cldn6, Cldn7 and prevents TJ formation and paracellular sealing at apical cell borders, inhibiting blastocyst formation ( 60 , 61 ). Knockdown of INO80 in porcine embryos impaired blastocyst development, paracellular sealing of TE, and decreased expression of OCT4, CDX2, TEAD4, CDH1, OCLN and several cell polarity, cytoskeleton and fluid-accumulation related genes ( 62 ).…”
Section: Adherens Junctionsmentioning
confidence: 99%
“…The placenta mediates exchanges between the maternal uterus and the fetus by supplying nutrients, producing hormones, eliminating waste products, and enabling gas diffusion via maternal blood circulation. In line with these functions, abnormalities in placental development are one of the key reasons for early pregnancy loss and are also responsible for many pregnancy-related diseases including preeclampsia [2][3][4] . Due to ethical considerations and difficulties in obtaining study material, the genetic regulatory mechanisms underlying the formation of human TE and early cytotrophoblast remain unclear.…”
mentioning
confidence: 99%